Analisis Keuntungan dan Efisiensi Usaha Keripik Pisang di Kabupaten Konawe - Devi Ayu Anggraini; Suharjo Suharjo; Milawati Saranani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze the benefits and efficiency of banana chips business in Konawe Regency. This study was conducted in Konawe Regency with a population of 5 people from Unaaha District, Amonggedo District, and Uepai District. The sample in this study was taken with the same number of respondents as the population, namely 5 people using the census method. Data sources consist of primary data and secondary data. Data collection techniques through interviews, observations, literature studies, and libraries and documentation. The data analysis method used in this study is to use cost analysis, revenue, profit, and Benefit/cost ratio or B/C ratio. The results of this study are that the banana chips business in Konawe Regency makes a profit of IDR 58,328,866/month with an average profit of IDR 11,665,773/month. While the average income is Rp 21,515,000/month and the average total cost is Rp 10,171,954/month. The results of the B/C ratio calculation obtained a B/C Ratio value of Rp 1.15 which shows that the results are greater than >1, meaning that every Rp. 1 cost incurred provides a profit of Rp 1.15. With the criteria of B/C value> 1, the banana chips business in Konawe Regency is productive or profitable and efficient to be worked on and developed.